Paradox Lost: Toward a Robust Test of the Chinese Learner - Morrison, Keith (Education Journal, 2006)
This article suggests that attempts to date to unravel the paradox of the Chinese learner are incomplete and inadequately modeled, and that the complexities of the paradox have not yet been fittingly operationalized or alternative explanations of research data investigated. It contends that attempts either to state or to unravel the paradox are chimerical, as they risk oversimplifying a complex phenomenon, the extent and nature of which are insufficiently understood to date. The article argues that investigating the phenomenon of Chinese learners' strong performance in international measures of achievement requires researchers to operate more rigorously in their search for alternative and multiple explanations of results in terms of causality, sampling, and representing heterogeneity. Several explanations of data on the paradox are presented, and alternative explanations which might be more usefully explored are provided. The article also questions the extent to which research on the Chinese learner, with a search for a unitary set of characteristics, is not, itself, prey to totalizing, collectivist ideologies cast in unrealistic meta-narratives. Recommendations are made for further research.